ANALISIS KOMBINASI PRODUK BATU ANGIN DAN PAVING STONE YANG OPTIMAL PADA CV. FRISKI PUTRO TERNATE - Rahmat Sabuhari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2013)
good entrepreneur is entrepreneur which can compare the sales revenue its production with the production cost, to determine the level production to give the maximum advantage to this company. The research aim to is know how much optimal combination product amount so that obtained by a maximum advantage and level of earnings contribution from two product. The result of analysis research simplex method is used.This research test the input use applied by company in producing stone o wind and paving stone earm the combination optimum, pursuant to calculation obtained by a yield uo the ghost petrify the wind as much 83 unit and paving stone as much 24 unit everyday which can give the contribution to earnings of a Rp. 140.200,-. This matter indicate that the circumstance have optimal pursuant to input use owned by company in this time. Finally on the part of head have to pay attention to the ots production activity, because company conition in this time face the very tight emulation from various other company.